Synthesis of Ni(II) porphyrazine peripherally 4-tert-butylbenzylthio moiety and electronic Schottky barrier diode octa-substituted with the properties of the Al/Ni(II)Pz/p-Si Schottky barrier diode - Keskin, Bahadir; Denktas, Cenk; Altindal, Ahmet; Avciata, Ulvi; Gul, Ahmet (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
Magnesium porphyrazinate substituted with eight 4-tert-butylphenylthio-groups on the peripheral positions has been synthesized by cyclotetramerization of 1,2-bis(4-tert-butylphenylthio)maleonitrile in the presence of magnesium butanolate. The metal-free derivative was obtained by its treatment with trifluoroacetic acid, and further reaction of this product with nickel(11) acetate led to the metal porphyrazinate (M = Ni). These new compounds have been characterized by elemental analysis, together with FT-IR. H-1 NMR and UV-Vis spectral data. The electronic properties of a spin coated film of NiPz have been studied by fabricating metal-insulator-semiconductor (MIS) capacitors. Current-voltage (I-V) and capacitance-voltage (C-V) measurements were carried out. It was observed that the Al/NiPz/p-Si structure exhibits rectifying behavior with a barrier height value of 0.89 eV and with an ideality factor value of 1.81. It was seen that this value of the obtained barrier height is remarkably higher than those given for metal/Si semiconductor contacts in the literature. The Lien, So and Nicolet method, combined with conventional forward I-V, was used to extract the series resistance value and it was found to be 26 k ohm. High frequency C-V measurements were used to determine the mobile oxide charge in the NiPz layer and this was found to be 1.6 x 10(11) cm(-2). (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Porphyrazine; Schottky barrier diode; Nickel; Thin films; Barrier height; Ideality factor; METAL-ION BINDING; PHTHALOCYANINES; COMPLEXES; SERIES; Chemistry; Crystallography